Navigating endodontic outcomes through cone-beam computed tomography: A narrative review - Shatha S. Zahran; Lujain H. Mirdad (Wolters Kluwer Medknow Publications, 2024)
Periapical radiographs (PRs) have been the most reliable modality for assessing periapical health. Later, the evolution of cone-beam computed tomography (CBCT) revolutionized three-dimensional maxillofacial skeletal imaging. CBCT imaging has emerged as a superior diagnostic tool compared to PR. The aim of this narrative review was to provide a comprehensive overview of the outcomes related to the use of CBCT in evaluating various endodontic treatments, including primary root canal treatments, secondary treatments, endodontic microsurgeries, and vital pulp therapies and the associated prognostic factors. The research selection process involved systematically searching PubMed, Scopus, and Web of Science for literature on CBCT and endodontics. Criteria included English-language; peer-reviewed articles published from January 2010 to December 2023, reporting 1-year outcomes of various endodontic treatments using CBCT. Two independent reviewers screened titles, abstracts, and full texts. A total of 18 outcome study articles utilizing CBCT to evaluate primary root canal treatment were selected, as well as 7 for secondary root canal retreatment, 3 for vital pulp therapy, and 11 articles pertaining to endodontic microsurgery. The outcomes revealed varying success rates and prognostic factors. Consistent with outcome research employing PRs, studies that utilized CBCT also exhibited substantial variability in factors affecting initial and secondary treatment outcomes. The rate of favorable outcomes was significantly lower when assessed with CBCT compared to PR. The results from utilizing CBCT for primary and secondary root canal treatments, endodontic microsurgeries, and vital pulp therapies demonstrate diverse success rates and prognostic factors in comparison to outcomes based solely on PRs.